Twenty years of in-situ monitoring in the south-eastern Mediterranean Levantine basin: Basic elements of the thermohaline structure and of the mesoscale circulation during 1995-2015 - Zodiatis, George; Brenner, Steve; Gertman, Isaac; Ozer, Tal; Simoncelli, Simona; Ioannou, Marinos; Savva, Sotiris (Frontiers in Marine Science, 2023)
The in-situ data gathered over two decades since mid-1990s in the South-Eastern Levantine Basin from 34 hydrographic campaigns and from 35 bi-weekly and monthly Voluntary Observing Ships (VOS) transects, after the pioneering POEM cruises, have provided insight on the dominant meso-scale coherent circulation features of this sub-basin. The most pronounced feature, the anticyclonic Cyprus Eddy, migrates over the broad region of the Eratosthenes seamount and exhibits significant seasonal and inter-annual spatial-temporal variability. Another prominent structure of the sub-basin is the anticyclonic Shikmona Eddy generated by instabilities of the strong northward flowing jet along the south-easternmost shelf and slope of the Levantine basin. Its evolution and co-existence with the Cyprus Eddy, cause the periodic re-establishment of the Shikmona Gyre, which was first observed during the POEM cruises in mid-1980s. The offshore, cross basin, eastward flowing Mid-Mediterranean Jet (MMJ) defines the northern and southern flanks of these sub-basin scale anticyclonic eddies and transports the lower salinity Modified Atlantic Water (MAW) in the subsurface layer, through the warmest and most saline waters of the Mediterranean. Periodically, the MMJ bifurcates and/or is diverted northward, along the western coast of Cyprus due to westward and northward spatial fluctuations of the Cyprus Eddy’s western boundaries. The current long term in-situ monitoring of the sub-basin provides an overview of the extent of the main water masses and characterizes their variability throughout the period considered. The analysis of the data indicates an increase of the temperature and salinity of the Levantine Surface Water (LSW) and of the subsurface MAW. The Eastern Mediterranean Transient Water (EMTW) is shown to occupy the deep cavities in the vicinity of the Eratosthenes seamount while its upper boundary was found to be lifted to shallower depths over a period of two decades.